The paradox of Nigeria higher education and the employment problem among youths: a critical analysis (2009)
This paper examined the problem relating to higher education and youth employment in the Nigerian labour market. The national survey data obtained from the Bureau of Statistics and other relevant government data bank formed the source of information for the research questions raised in the study. The data were analysed using the simple descriptive statistics. Findings showed that the signals from the Nigerian labour market were becoming more precarious than ever before owing to the growing unemployment problem among youth graduates from the various higher institutions of learning. It revealed that there was a paradox between Nigerian higher education and the labour market. The paradox was that, while graduates supply increased from the various higher institutions over time, there were shortages of relevant and required labour force needed by the labour market for meaningful development. The study concluded that there was a growing mismatch between higher education output and the labour market demand. It therefore recommends that higher education should respond to the changing challenges by directing attention to generic competencies and skill development of students and prepare them for the growing globalisation beyond the usual classroom teaching and learning